Speech by Yang Amat Berhormat Ketua Menteri Pulau Pinang Dr Lim Chong Eu at the official opening of the new Township of Seberang Jaya on the 11th October 1976 by Yang Amat Berhormat Datuk Hussein Onn Perdana Menteri Malaysia. - Lim, Chong Eu (1976)
On behalf of the State Government of Penang,I welcome all of you to the official opening of the new Township in Seberang Perai.